Implementasi Peraturan Kepala Perpustakaan Nasional RI Nomor 13 Tahun 2017 tentang Standar Nasional Perpustakaan Perguruan Tinggi di UPT Perpustakaan Universitas Bung Hatta - Mutiara Atika; Ardoni Ardoni; Gustina Erlianti; Jeihan Nabila (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to describe the following. (1) implementation of collection standards at Bung Hatta University Library (2) implementation of facilities and infrastructure standards at Bung Hatta University Library (3) implementation of service standards at Bung Hatta University Library (4) implementation of library promotion standards at Bung Hatta University Library (5) implementation of library staff standards at Bung Hatta University Library, and (6) implementation of information and communication technology standards at Bung Hatta University Library. The research methodology used is qualitative research with the type of Field Research research and uses a descriptive approach. Data collection techniques through observation, interviews, and documentation. The informants in this study were one library officer and two people from the library users at the Bung Hatta University Library. Based on the results of the study, it can be concluded as follows. First, the implementation of collection standards, consisting of nine sub-indicators, of the nine sub-indicators, there are six sub-indicators that meet standard implementation and three sub-indicators that do not meet standard implementation. Second, the implementation of facilities and infrastructure standards, consisting of five sub-indicators, of the five sub-indicators, there are two sub-indicators that meet the implementation of standards and three sub-indicators that have not met the implementation of standards. Third, the implementation of service standards, consisting of two sub-indicators, of the nine sub-indicators, there is one sub-indicator that meets the implementation of standards and one sub-indicator has not met the implementation of standards. Fourth, the implementation of library promotion standards, this indicator has met the standard implementation. Fifth, the implementation of library staff standards, consisting of three sub-indicators, of the three sub-indicators, there is one sub-indicator that meets the standard implementation and two sub-indicators have not met the standard implementation. Sixth, the implementation of information and communication technology standards, this indicator has not met the implementation of standards. Thus, of the twenty-one sub-indicators assessing the implementation of the Regulation of the Head of the National Library of the Republic of Indonesia Number 13 of 2017 concerning National Library Standards at the UPT Library of Bung Hatta University, those that meet the National Standards for Higher Education Libraries based on the Regulation of the Head of the National Library of the Republic of Indonesia Number 13 of 2017 concerning National Standards for Higher Education Libraries are 11 sub-indicators and those that have not met the standards are 10 sub-indicators.